A review on batch and column adsorption of various adsorbent towards the removal of heavy metal - Sazali, Norsuhailizah; Harun, Zawati; Sazali, Norazlianie (Penerbit Akademia Baru, 2020)
The batch adsorption and column adsorption performance of various adsorbent towards the removal of heavy metal are critically reviewed. Fundamental ideas of adsorption, including chemical adsorption and physical adsorption and its component, adsorbents, and adsorbates, are incorporated. The adsorption study using various adsorbates, i.e., heavy metal (Cr, Cd, Pb, Ni, and Cu), are inspected. A set of various design experiment for batch and column adsorption are discussed deeply for removal of heavy metal. Differentiation between batch and column adsorption study are referenced. This paper explains deeply on clarification of different parameters, in both batch and column adsorption. The various parameter for column adsorption, i.e., inlet ion concentration, flow rate, bed height and for batch adsorption, i.e., contact time, pH, temperature, and adsorbent dose, are completely covered. The isotherm model, and kinetic model for both adsorptions are well described. Besides, a breakthrough curve for designing the column adsorption is completely observed. In the end, some difficulties for adaptation both adsorption in the real world are revealed.